Parasocial Communication with Digital Influencers: A Communication Science Perspective on Virtual Proximity (Journal of Dialogos, 2026)
Parasocial communication with digital influencers has become a significant phenomenon within the contemporary social media landscape. This study aims to examine the mechanisms underlying parasocial relationship (PSR) formation between audiences and digital influencers, including AI-generated virtual influencers, and their implications for consumer behavior and psychological well-being. Through a systematic literature review of 20 internationally peer-reviewed journal articles (2021–2025), the study identifies key mediating factors of virtual proximity: source credibility, self-disclosure, self-discrepancy, social presence, trust, and authenticity perception. Results indicate that micro- and nano-influencers generate stronger parasocial bonds than mega-influencers (mean PSR = 4.35 vs 3.42). The integration of virtual influencers adds complexity to these relations through dimensions of origin uncertainty and anthropomorphism. The study contributes by proposing the Integrative Digital Parasocial Model (IDPM), which maps the pathway from content characteristics to behavioral responses via relational mediators.